Hydrophobicity of small alkane molecules (propane dimer) in solvents: a classical molecular dynamics study - Panthi, Bikash; Pantha, Nurapati (BIBECHANA, 2020)
Molecular Dynamics (MD) simulations of propane dimer in different solvents (water, acetonitrile and methanol) were performed by using CHARMM platform for modeling the solute and solvents. A series of Umbrella sampling MD simulations were carried out in each solvent separately and potential of mean force (PMFs) were calculated by using Weighted Histogram Analysis Method. Results show that two minima (contact minima and solvent separated minima) characterize the PMF of propane dimer in all three solvent environments. The contact minima are deeper and less sensitive to solvent environment for its position. However, significant effect in the position of second minima, solvent separated minima, was observed. Our study reveals that the interaction between propane dimer is softer in methanol and acetonitrile than in water. BIBECHANA 17 (2020) 1-12